Shantali Language: Its origin and linguistic characteristics - Murshed, Sikder Monoare (Dhaka University Journal of Linguistics, 2009)
Approximately three lakh Santali inhabit the northern region of Bangladesh (NB), namely, Rajshahi, Nawgaon, Dinajpur, Bogura, Rangpur, Thakurgaon etc. In terms of the Santali language there are 52 lakh speakers in the world, concentrated primarily in the region if India, Bangladesh and Nepal. Devoid of a script of its own the Santali language has been handed down generation after generation orally. However, the first written forms of Santali can be found in the Roman script, written by the Christian missionaries. However, the Bangla script was used for Santali education. The Santali language belongs to the Mundari branch of the Austro-Asiatic language family. Although there have been sparse attempts to study the language of the Santals, no research work on the origin and linguistic features of Santali can be found in Bangladesh. This article discusses the origin of Santali and presents a linguistic analysis of its characteristic features. Dhaka University Journal of Linguistics Vol.1(1) 2008